Health communication messaging about HPV vaccine in Papua New Guinea. (December 2019) - Kelly-Hanku, Angela; Newland, Jamee; Aggleton, Peter; Ase, Sophie; Fiya, Voletta; Aeno, Herick; Vallely, Lisa M; Mola, Glen DL; Kaldor, John M; Vallely, Andrew J
Objective: The type of health education messages that communities and individuals seek to have communicated about the human papillomavirus (HPV) vaccine is important if vaccine programmes are to succeed, especially in settings such as Papua New Guinea (PNG), which have a high burden of cervical cancer, low health literacy and negative experiences of earlier vaccination programmes. This study sought to identify the health education messages that are viewed as most appropriate in such a context. Methodology: A qualitative study using gender-specific focus group discussions ( N  = 21) and semi-structured interviews ( N  = 82) was undertaken in three sites in PNG. Sites included both rural and urban locations in Milne Bay, Eastern Highlands and Western Highlands Provinces. Results: Two divergent discourses emerged. One group of participants, largely young people, felt communication messages should stress that HPV is a preventable sexually transmitted infection, which can cause cervical cancer. The other group, mainly members of the older population, believed that messaging should focus on the vaccine as a prevention strategy for cervical cancer. A small minority wanted both aspects of the vaccine discussed. Conclusion: Sensitivity needs to be taken when engaging with communities which have negative experiences of earlier infant immunisation programmes. Ensuring that the health communication needs and priorities of different sections of the populations are taken into account is key to the successful introduction and roll-out of HPV vaccination in this setting.